2019
DOI: 10.1112/blms.12267
|View full text |Cite
|
Sign up to set email alerts
|

On C∗‐completions of discrete quantum group rings

Abstract: We discuss just infiniteness of C * -algebras associated to discrete quantum groups and relate it to the C * -uniqueness of the quantum groups in question, that is, to the uniqueness of a C * -completion of the underlying Hopf * -algebra. It is shown that duals of q-deformations of simply connected semisimple compact Lie groups are never C * -unique. On the other hand, we present an example of a discrete quantum group which is not locally finite and yet is C * -unique.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…those for which the corresponding Hopf algebra is finitedimensional; ‚ Quantum permutation groups, i.e. quantum subgroups of S Ǹ for N P N (this includes for instance the quantum reflection groups H sǸ for all 1 ď s ă `8); ‚ Profinite compact quantum groups in the sense of [CDPR14], or in the terms of [CS19], duals of locally finite discrete quantum groups. Note also that [CDPR14] gives examples of duals of discrete groups which are totally disconnected as compact quantum groups, hence totally strongly disconnected, but not profinite.…”
Section: 2mentioning
confidence: 99%
“…those for which the corresponding Hopf algebra is finitedimensional; ‚ Quantum permutation groups, i.e. quantum subgroups of S Ǹ for N P N (this includes for instance the quantum reflection groups H sǸ for all 1 ď s ă `8); ‚ Profinite compact quantum groups in the sense of [CDPR14], or in the terms of [CS19], duals of locally finite discrete quantum groups. Note also that [CDPR14] gives examples of duals of discrete groups which are totally disconnected as compact quantum groups, hence totally strongly disconnected, but not profinite.…”
Section: 2mentioning
confidence: 99%
“…Example 2.8. [7,Proposition 2.4] showed that a compact quantum group is coamenable if and only its reduced C * -algebra admits a finite-dimensional representation. Therefore, using the results of Banica from [1], [2] and [3]…”
Section: Cqg-algebraic Quotients Vs C*-algebraic Quotientsmentioning
confidence: 99%